PENGARUH BIAYA TRANSPORTASI DAN BIAYA PEMASARAN TERHADAP LABA BERSIH PADA PT. SINAR ANDESTO MANDIRI LOGISTIK - Amran, Kiagus Muhammad; Diawati, Prety; Lubis, Nur Iqra Putri (Universitas Logistik dan Bisnis Internasional, 2025)
Transportation is a business or activity by carrying goods, passengers from one place to another. Efforts to market products, both goods or services, using planning and systematic methods so that they can increase the number of sales are called marketing. Net profit is the amount of difference between income exceeding expenses (expenses). The study aims to explain